Food Additives 2017
DOI: 10.5772/intechopen.69284
|View full text |Cite
|
Sign up to set email alerts
|

Waste Degradation and Utilization by Lactic Acid Bacteria: Use of Lactic Acid Bacteria in Production of Food Additives, Bioenergy and Biogas

Abstract: Lactic acid bacteria (LAB) are one of the most well-studied bacterial groups known from ancient times. These valuable microorganisms are used in numerous areas, especially food industry and medicine. LAB produce a wide range of compounds for food upgrading. Moreover, LAB can find special applications like generation of bioenergy not affecting the surrounding environment. The article considers physiological and biochemical processes determining valuable characteristics of the bacteria, potential applications of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 215 publications
(197 reference statements)
0
19
0
Order By: Relevance
“…Consequently, it has wide applications in medicine and food processing. Nowadays, lactic acid bacteria have been found to play an important role in agriculture, bioenergy production, and bioremediation of the environment [46]. In the present study we, firstly, aimed to stabilize alfalfa brown juice through reducing its water-soluble sugars content and pH using lactic acid bacteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, it has wide applications in medicine and food processing. Nowadays, lactic acid bacteria have been found to play an important role in agriculture, bioenergy production, and bioremediation of the environment [46]. In the present study we, firstly, aimed to stabilize alfalfa brown juice through reducing its water-soluble sugars content and pH using lactic acid bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, organic acids (e.g., lactic, acetic, and propionic acids) were increased in fermented brown juice causing a subsequent reduction in pH (Table 1). Novik, et al [46] reported lactic acid as the main acid produced after fermentation of water-soluble sugars such as glucose and fructose either monomer or oligomer by lactic acid bacteria. Similar findings were cited by Bautista-Trujillo et al [48], who observed a decrease in pH of maize silage after inoculation by lactic acid bacteria due to the increase in the production of organic acids, mainly lactic and acetic acids.…”
Section: Discussionmentioning
confidence: 99%
“…However, pre‐acidic or alkaline treatment is costly, environmentally unfriendly and unsuitable for the ensiling process (Keller et al ). Alternatively, the use of LB can make the biosilage process simpler, faster, more environmentally friendly and cost‐efficient than chemical technology (Novik et al ). Before, recommending LB for use, in vitro digestion is needed.…”
Section: Discussionmentioning
confidence: 99%
“…The ability to ferment C5 sugars is a feature of heterofermentative LAB, which utilizes those sugars through the pentosophosphate pathway. This process leads to the production of acetic acid 32 . In this process, xylose is first isomerized by xylose isomerase (XylA) to xylulose, which is further phosphorylated to xylulose-5-phosphate (X5P) by xylulokinase (XylB).…”
Section: Discussionmentioning
confidence: 99%